2017
DOI: 10.1093/eurpub/ckx181
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on the use and outcomes of maternal and child healthcare services by undocumented migrants in Europe

Abstract: Despite major methodological differences between included studies, the results of this review indicate that the status of undocumented migrants exacerbates known health risks and hampers service use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 26 publications
4
65
0
Order By: Relevance
“…As previous studies in the country have shown [7], these women experience unstable employment conditions and di culties accessing health care services due to their irregular status. This situation has been observed in other studies conducted on the immigrant population, con rming the vulnerability of this group [25]. Being pregnant, together with economic di culties and their status as irregular immigrants, hinders their empowerment and places them in a situation of social and emotional dependence on other people and sometimes their partners.…”
Section: Discussionsupporting
confidence: 63%
“…As previous studies in the country have shown [7], these women experience unstable employment conditions and di culties accessing health care services due to their irregular status. This situation has been observed in other studies conducted on the immigrant population, con rming the vulnerability of this group [25]. Being pregnant, together with economic di culties and their status as irregular immigrants, hinders their empowerment and places them in a situation of social and emotional dependence on other people and sometimes their partners.…”
Section: Discussionsupporting
confidence: 63%
“…The health of migrant children depends on their health status before their journey, the conditions during their journey and various forms of the trauma they may experience including war, violence, separation from their family, and exploitation. 1,10 Although the UN gathered in New York for a summit (on September 19, 2016) to agree on a "coordinated and humane approach" to the migrant and refugee issue, the truth is that migrants experience violent events such as physical violence by authorities in 13% of the cases, bad treatment by smugglers in 11%, kidnapping in 6%, and violence by the community in 5% of the cases. 6,11 In this study, no migrant ever reported violence as a trauma cause; however, due to their living conditions and their mistrustful relations toward authorities, in our opinion, violence cannot be ruled out with certainty.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally care affordability has been identified as a challenge for undocumented pregnant mothers in countries that do not provide free care to this group [22]. Women in most of…”
Section: Other Factorsmentioning
confidence: 99%